2004
DOI: 10.1111/j.1365-3016.2004.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical exposures during pregnancy and congenital cardiovascular malformations

Abstract: Congenital cardiovascular malformations (CCM) cause substantial neonatal morbidity and mortality. Known risk factors for CCM explain only 10-20% of all cases. Few studies have examined mothers' physical exposures during pregnancy and the risk of CCM in their offspring. This study examined the association between exposures to extreme temperatures, prolonged standing, and heavy lifting during early pregnancy and risk of CCM in offspring. Using a case-control study design, 502 cases and 1066 controls were drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…No association was found between maternal sauna REVIEW bathing, the course of gestation, or the occurrence of congenital defects in a Finnish study (a three-year national material with about 500 cases and 1000 healthy control babies) (49). Similar results on the use of hot baths and sauna have been reported from New York (50). Nor was the risk increased in Finland for defects of the central nervous system and of orofacial clefts (51), or heart defects (49).…”
Section: Pregnancysupporting
confidence: 67%
“…No association was found between maternal sauna REVIEW bathing, the course of gestation, or the occurrence of congenital defects in a Finnish study (a three-year national material with about 500 cases and 1000 healthy control babies) (49). Similar results on the use of hot baths and sauna have been reported from New York (50). Nor was the risk increased in Finland for defects of the central nervous system and of orofacial clefts (51), or heart defects (49).…”
Section: Pregnancysupporting
confidence: 67%
“…In contrast, studies in Flyde of Lancashire (Bound et al, 1989) and Finland (Tikkanen and Heinonen, 1993) found no evidence of seasonal variation in coarctation of the aorta, which could be due to geographical differences in associations. An occupational study in New York State showed no relationship between congenital heart defects and maternal self-reported number of hours per week spent in temperatures less than 01 F ( À18 1C) (Judge et al, 2004); however, all congenital heart defects were grouped together and coarctation of the aorta represents less than 10% of heart defects (O'Brien, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Exposure to "too cold" environmental conditions at work was associated with spontaneous abortion in one study (McDonald et al, 1988). An occupational study in New York State showed no relationship between congenital heart defects and time Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/envres spent in environments with temperatures less than 0 1F (À18 1C) (Judge et al, 2004). In a study of congenital heart defects in Tel-Aviv Israel, a 1-day increase in extreme heat events in the cold season was associated with multiple congenital heart defects and isolated atrial septal defects (Agay-Shay et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Two of these studies reported elevated odds ratios (ORs) (Milunsky et al, 1992;Suarez et al, 2004) and two reported no elevation in risk (Chance, 1978;Saxen et al, 1982). Three studies assessed the association between hot tub or sauna use and heart defects and found no association (Judge et al, 2004;Saxen et al, 1982;Tikkanen and Heinonen, 1991). Based on data from the National Birth Defects Prevention Study, we examined the effects of hot tub use for 17 major phenotypes of noncardiac birth defects.…”
Section: Introductionmentioning
confidence: 96%